Cardiovascular risk factors: differences between ethnic groups - Toledo, Noeli das Neves; Almeida, Gilsirene Scantelbury de; Matsuura Matos, Miharu Maguinoria; Silva Balieiro, Antonio Alcirley da; Martin, Luis Cuadrado [UNESP]; Silva Franco, Roberto Jorge da [UNESP]; Therese Mainbourg, Evelyne Marie (Assoc Brasileira Enfermagem, 2020)
Objectives: to compare the metabolic, anthropomenic, tobacco and alcohol consumption indicators considered as risk factors for cardiovascular diseases, as well as the demographic and socioeconomic characteristics between indigenous from Rio Negro, Satere-Nlawe, mixed-race/ black and white people living in the city of Manaus. Methods: a cross-sectional observational study guided by the STROBE tool.Thee was a sample of 191 adults of both sexes. Anthropometric measurements, blood pressure and biochemical analyzes were performed. Statistical test was applied to cross color/race/ethnicity variable with the investigated variables. Results: indigenous had better metabolic and anthropornetric indicators related to cardiovascular diseases than mixed-race/bladc and white, as well as Satere-Mawe in relation to Rionegrinos (from Rio Negro). Conclusions: the main differences were obesity, dyslipidemia, pre-systemic arterial hypertension/ systemic arterial hypertension, and increased circumferences, with a worse situation for mixed-race/black people. The findings indicate differences in risk factors between race/color and ethnicity groups evaluated.
Keywords: Cardiovascular Diseases; Risk Factors; Indigenous Population; Ethnic Groups; Urban Population